Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session “Nutrition of the preterm infant” - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2018)
Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session “Nutrition of the preterm infant” ABS 1. EARLY VERSUS DELAYED PHOSPHOROUS SUPPLEMENTATION IN PREMATURE NEONATES • C. Bazacliu, K. O’Mara ABS 2. ASSOCIATION OF EXCLUSIVE HUMAN MILK FEEDING AND NECROTIZING ENTEROCOLITIS IN VERY LOW BIRTH WEIGHT NEONATES • A. Patel, Y. Kandasamy ABS 3. PERIPHERAL VENOUS CATHETER (PVC) VS PERIPHERALLY INSERTED CENTRAL VENOUS CATHETER (PICC) FOR VERY LOW BIRTH WEIGHT NEWBORNS. A RANDOMISED TRIAL • I. Aldakauskiene, R. Tameliene, R. Brinkis, R. Kevalas ABS 4. MACRONUTRIENT COMPOSITION OF HUMAN MILK DEPENDING ON DIFFERENT GESTATIONAL AGE AT BIRTH • I.J. Paulaviciene, A. Liubsys, L. Tamuliene, A. Molyte, V. Usonis ABS 5. NUTRITION AND NEURODEVELOPMENTAL OUTCOME AT 2 YEARS OF AGE: INVESTING IN THE FIRST 1,000 DAYS • A. Katana, R. Mardare, S. Luyima, N. Merchant ABS 6. CAN WE PREDICT AND PREVENT OSTEOPENIA OF PREMATURITY? • P. O’Reilly, A. Tou, M. Saviani, N. McCallion ABS 7. CHARACTERISTICS OF NEWBORNS FED EXCLUSIVELY WITH THEIR MOTHERS’ OWN MILK: AN OBSERVATIONAL STUDY IN THE NICU • J. Witek, I. Kedzior, M. Kostro, A. Kowal, A. Wesołowska, T.E. Bachman, M. Wilinska ABS 8. PROTEIN CONTENT OF FRESH HUMAN MILK AND VARIABILITY RELATED TO PRESERVATION METHODS IN THE NICU • L. Păduraru, G.I. Zonda, A.L. Avasiloaiei, M. Moscalu, D.C. Dimitriu, M. Stamatin ABS 9. RIB FRACTURE INCIDENCE, DO PRETERM BONES STILL BREAK? • P. O’Reilly, M. Saviani, A. Tou, N. McCallion ABS 10. THE IMPACT OF FEEDING INTERVAL ON TIME TO ACHIEVE FULL ORAL FEEDING IN PRETERM INFANTS • S. Unal, N. Demirel, A.Y. Bas, İ. Arifoğlu, S. Erol, D. Ulubas-Isik ABS 11. AUDIT OF VITAMIN D (VD) LEVELS AND INTAKES IN THE NEONATAL UNIT • S. Clark, C. King, H. Speckmeier ABS 12. COMPUTERIZED NUTRITION PROGRAM USED TO IMPROVE NUTRITION IN EXTREMELY LOW BIRTH WEIGHT INFANTS • C. Zgârcea, E. Stoicănescu, R. Dumitra, O. Boantă, E. Călin, M.L. Ognean ABS 13. DOES OSMOLALITY CHANGE WHEN INFANT FORMULA IS FORTIFIED WITH DEXTRIN MALTOSE FOR MANAGEMENT OF ASYMPTOMATIC HYPOGLYCEMIA? • F.Z. Chioukh, T. Khemis, K. Ben Ameur, N. Ladib, H. Ben Hmida, K. Monastiri ABS 14. FEEDING DIFFICULTIES FOLLOWING NEONATAL CARDIAC SURGERY • X. Agrogianni, M. Prapa, S. Tzalavra, G. Kalavrouziotis, T. Konitsioti ABS 15. FIRST-YEAR EXPERIENCE OF DONOR MILK BANK AT THE VILNIUS PERINATAL CENTRE • L. Tamuliene, I.J. Paulaviciene, A. Liubsys ABS 16. MOTHERS’ OWN BREAST MILK FOR ELBW INFANTS: PASTEURIZED OR NOT? • P. Bitouni, A. Kapetanaki, E. Koutsounaki, G. Liosis, H. Salvanos, M. Tzaki ABS 17. OBSERVATIONAL STUDY OF VITAMIN D (VD) INTAKES AND LEVELS ON THE NEONATAL UNIT • S. Clark, C. King, H. Speckmeier ABS 18. RISK FACTORS FOR EXTRAUTERINE GROWTH RESTRICTION IN EXTREMELY LOW BIRTH WEIGHT PRETERM INFANTS • M.L. Ognean, C. Zgârcea, E. Stoicănescu, O. Boantă, E. Decean, E. Călin ABS 19. SOCIAL AND EPIDEMIOLOGICAL FACTORS CONTRIBUTING TO MICROBIOLOGICAL CONTAMINATION OF THE HUMAN DONOR’S MILK • E. Lysoviene, U. Dumbliauskaite, P. Aldakauskaite, V. Ivanauskiene, R. Tameliene ABS 20. EFFECT OF FORTIFICATION ON THE OSMOLARITY OF INFANT MILK FORMULA • F.Z. Chioukh, T. Khemis, K. Ben Ameur, A. Chaabane, I. Dhouibi, M.A. Kotti, M.A. Lassoued, H. Ben Hamida, N. Laadib, S. Sfar Gandoura, K. Monastiri ABS 21. ENTERAL NUTRITION IN EXTREMELY LOW BIRTH WEIGHT NEWBORNS • A. Manea, D. Cioboata, F. Doandes, O. Costescu, N. Lungu, M. Boia ABS 22. IS HYPOPHOSPHATEMIA A RISK FACTOR FOR METABOLIC BONE DISEASE? • L. Blaga, M. Matyas, C. Vidra, M. Hasmasanu, G. Zaharie ABS 23. THE EFFECT OF INTERMITTENT AND CONTINUOUS FEEDING ON GROWTH AND TIME TO DISCHARGE IN VERY LOW BIRTH WEIGHT INFANTS • M. Selalmaz, G. Uysal, A. Bulbul ABS 24. ANTENATAL AND POSTNATAL ASPECTS OF PRETERM NEWBORNS WITH AND WITHOUT INTRAUTERINE GROWTH RESTRICTION • S.M. Stoicescu, L. Radulescu ABS 25. NEONATAL NECROTIZING ENTEROCOLITIS: SHORT-TERM PROGNOSIS • H. Ben Hmida, F.Z. Chioukh, T. Khemis, M. Zghal, K. Ben Ameur, A. Hellara, K. Monastiri ABS 26. THE EFFECT OF BREASTFEEDING ON MATERNAL CARDIOVASCULAR HEALTH • A. Belegrinos, D. Belegrinos, A. Giannakopoulou ABS 27. DURATION OF BREASTFEEDING AND FACTORS ASSOCIATED WITH EARLY BREASTFEEDING CESSATION IN A TUNISIAN POPULATION • F.Z. Chioukh, A. Chaabane, M. Bizid, T. Khemis, N. Ladib, I. Dhouibi, H. Ben Hmida, K. Ben Ameur, K. Monastiri ABS 28. DETERMINANTS OF NEONATAL VITAMIN D STATUS IN PRETERM INFANTS AT BIRTH – CROSS-SECTIONAL STUDY • E. Głuszczak-Idziakowska, M. Zarlenga, M. Wilińska, J. Czech-Kowalska, M. Tałałaj, G. Jakiel, M. Skrzypek ABS 29. SERUM ALUMINUM LEVEL IN PRETERM INFANTS: IS IT IMPORTANT? • A. Bulbul, S. Bahar, U. Zubarioglu, S. Uslu, A. Koc Bebek ABS 30. PROBIOTIC SUPPLEMENTATION IN TERM NEWBORNS DELIVERED BY CESAREAN SECTION: A RANDOMIZED, PROSPECTIVE CLINICAL TRIAL • J. Hurkała, R. Lauterbach, R. Radziszewska, K. Hadała, P. Heczko